The first observation of Hb D Punjab beta zero thalassaemia in an English family with 22 cases of unsuspected beta zero thalassaemia minor among its members. - Worthington, S (1985)
A 36 year old local Englishman from Nuneaton was referred to hospital with suspected glandular fever. Relevant tests were negative and the symptoms subsided in due course. The finding of a hypochromic microcytic blood picture without iron deficiency led to the discovery that he was heterozygous for Hb D and beta thalassaemia. Hb D trait was established in the father of the proband and beta thalassaemia in his mother and a brother. The father's ancestors were miners who came to Nuneaton from Monmouthshire in the 19th century. The mother's ancestors have belonged to the indigenous population of Nuneaton and neighbouring Leicestershire since the 18th century. Twenty local members of her wider family also had thalassaemia. All thalassaemias had a low MCH and raised level of Hb A2. The Hb F level, however, was normal in five, demonstrating the independent segregation of genetic factors influencing the Hb F level in beta thalassaemia trait.